Analisis Yuridis Penghentian Tunjangan Kinerja bagi Anggota Polri yang Dijatuhi Hukuman Demosi - Nikodimus Valentino; Lukman Hakim; Lusia Sulastri (Jurnal Global Futuristik, 2026)
The termination of performance allowances for members of the Indonesian National Police who receive demotion sanctions is the focus of this study. Legal issues arise because this practice refers to internal directives and instructions that have not yet been recognized as valid legislation. Using a normative approach, an analysis was conducted on regulations and principles of administrative law to examine the legality of this policy. Presidential Regulation Number 103 of 2018 concerning Performance Allowances for Employees within the Indonesian National Police and Regulation of the Head of the Indonesian National Police Number 7 of 2020 concerning Procedures for Providing Performance Allowances for Employees within the Indonesian National Police both do not contain explicit provisions regarding the termination of performance allowances due to demotion. Policies based on internal directives also lack general legal binding force. Potential violations of the principles of legality, legal certainty, and proportionality arise from this situation. A reconstruction of the policy based on clear and proportional regulations is emphasized as a necessity in this study.